Unhealthy Secessionist Agitations in South-Eastern Nigeria and Implications on National Security - Abiodun, Temitope Francis; Oladele, Clement O. (International Journal of Conflict Management, 2024)
Purpose: The purpose of this study was to examine the secessionist agitations; implications on Nigeria's national security; and strategies of managing the challenges. Specifically, the study was anchored on the following objectives; Public awareness, Capacity building and Policy implementation. Methodology: The researchers adopted Ted Gur's Theory of Deprivation and the descriptive design for the study. Primary and secondary data were obtained. Primary data were collected through the 17 interviews held with the purposely-selected respondents from the in selected South Eastern states of Nigeria, comprising (Enugu, Abia and Anambra) because of the prevailing calls for secessionist agitations in the areas. The secondary source of data included; the existing literatures, relevant journal publications, dailies, magazines and web materials. Data obtained were content-analyzed. Findings: Findings of the study revealed that the call for self-determination and restructuring pursuant to the nature of country, where good governance is obviously absent, remain parts of the notable causes of secessionist agitation while the struggles have impacted negatively the national security of Nigeria. However, the paper reveals that the instances of secessionist threats in the country have led to all forms of insecurity in the land region, thus resulting in the restrictions of people's movement and also threats to human lives and property. The study therefore recommends there is need for hands-on policies put in place and implemented in relation to the developmental demands of the masses traversing the conflict-proven locations of secessionist agitators for amicable remedies to the growing menace in Nigeria. Unique contribution to theory, practice and policy: The study identifies the gap that lies between policy implementation, the call for self-determination and restructuring pursuant to the nature of country, where good governance is obviously absent, remain parts of the notable causes of secessionist agitation while the struggles have impacted negatively the national security of Nigeria. There are still gaps to be filled in awareness campaign, capacity building and policy implementation on the need for hands-on policies to be put in place and implemented in relation to the developmental demands of the masses traversing the conflict-proven locations of secessionist agitators for amicable remedies to the growing menace in Nigeria.